Radiological Correlates of Raised Intracranial Pressure in Children: A Review - Kayhanian, Saeed; Young, Adam M. H.; Piper, Rory J.; Donnelly, Joseph; Scoffings, Daniel; Garnett, Matthew R.; Fernandes, Helen M.; Smielewski, Peter; Czosnyka, Marek; Hutchinson, Peter J.; Agrawal, Shruti (Frontiers in Pediatrics, 2018)
Radiological assessment of the head is a routine part of the management of traumatic brain injury (TBI). This assessment can help to determine the requirement for invasive intracranial pressure (ICP) monitoring. The radiological correlates of elevated ICP have been widely studied in adults but far fewer specific paediatric studies have been conducted. There is, however, growing evidence that there are important differences in the radiological presentations of elevated ICP between children and adults. This is a reflection of anatomical and physiological differences, as well as a difference in the pathophysiology of brain injury in children. Here in, we review the radiological parameters that correspond with increased ICP in children that have been described in the literature. We then describe the future directions of this work and our recommendations in order to develop non-invasive and radiological markers of raised ICP in children.